2022
DOI: 10.5653/cerm.2022.05302
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of polyglycolic acid as an animal-free biomaterial for three-dimensional culture of human endometrial cells

Abstract: Objective: Animal-free scaffolds have emerged as a potential foundation for consistent, chemically defined, and low-cost materials. Because of its good potential for high biocompatibility with reproductive tissues and well-characterized scaffold design, we investigated whether polyglycolic acid (PGA) could be used as an animal-free scaffold instead of natural fibrin-agarose, which has been used successfully for three-dimensional human endometrial cell culture. Methods: Isolated primary endometrial cells was cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…A three-dimensional (3D) poly(lactic-co-glycolic acid)(PLGA)/poly (e-caprolactone) (PCL) scaffold based on wet-electrospinning [56] that consisted of a very loose, dispersive, and randomly oriented porous fiber structure for cell population and differentiation [57], and eventually for the generation of osteochondral (bone) tissue, was developed via the endochondral approach [58]. Layered natural endometrial stromal cells were cultured in a 3D PGA electrospun scaffold in which an electrospun nanoweb was overlaid by a monolayer of endometrial epithelial cells, and it was found that the overall arrangement was identical to the native endometrium [59].…”
Section: Introductionmentioning
confidence: 99%
“…A three-dimensional (3D) poly(lactic-co-glycolic acid)(PLGA)/poly (e-caprolactone) (PCL) scaffold based on wet-electrospinning [56] that consisted of a very loose, dispersive, and randomly oriented porous fiber structure for cell population and differentiation [57], and eventually for the generation of osteochondral (bone) tissue, was developed via the endochondral approach [58]. Layered natural endometrial stromal cells were cultured in a 3D PGA electrospun scaffold in which an electrospun nanoweb was overlaid by a monolayer of endometrial epithelial cells, and it was found that the overall arrangement was identical to the native endometrium [59].…”
Section: Introductionmentioning
confidence: 99%